Development of Aspect and Tense in Semitic Languages: Typological Considerations - Bubenik, Vit (Lingua Posnaniensis, 2012)
A survey of pertinent literature reveals that many studies of aspect in Semitic languages do not pay a due attention to the crucial theoretical distinction of perfect and perfectivity. In this paper I will adopt the ‘chronogenetic' model of the morphosyntactic development of tense and aspect tested for the Indo-European languages (Hewson & Bubenik 1997) that allows five major aspectual categories to be distinguished (prospective, inceptive, imperfective, perfective, perfect) within ‘Event Time’. I will argue that the appearance in Arabic of the analytic double-finite perfect (of the type kun-tu katab-tu ‘I had written’) was the most significant innovation during the New Stage not to be found in the other Central Semitic languages. During the Middle Stage in Mishnaic Hebrew and Middle Aramaic the canonical progressive aspect was paradigmatized while Classical Arabic created its double-finite counterpart (kān-a ya-ktub-u ‘he was writing’). The significance of this approach to the study of the universals of tense and aspect will be evaluated.